Survey Of Mulberry Diseases In Different Mulberryvarieties Of North Eastern Region Of Uttar Pradesh (Journal of Plant Disease Sciences, 2021)
A field survey was carried out in the North Eastern region of Uttar Pradesh to record the disease incidence on Mulbery plantations of various varieties. Powdery mildew (Phyllactinia corylea), Leaf spot (Cercospora moricola), Rust (Cerotelium fici) and Bacterial blight (Pseudomonas syringae pv. mori) were prominently observed on mulberry varieties grown in the area. Seasonality wise highest percentage of diseased incidence was observed during spring, summer, monsoon and autumn seasons. Highest infection (63.7 ± 0.92) of powdery mildew was observed in the S146 mulberry variety and least (13.51 ± 0.78) was in V1 variety. The disease incidence of leaf spot infection was found to be 26.41 ± 1.78 in the S146 mulberry variety and 6.25± 0.02 in the V1 variety. The disease incidence of leaf rust infection was highest in TR10 mulberry variety (8.92±2.26), and lowest in S1 variety (0.77±1.02). The bacterial infection of disease incidence was highest (11.86 ± 1.27) in AR14 mulberry variety and lowest was 2.77 ± 0.96 in S146 in mulberry variety.
Keywords: Diseases; Field survey; Mulberry; Varieties